Educational Technology: from the Digital Classroom - Dwiyanto (EduTech Journal, 2025)
This study aims to examine the implementation of educational technology in the context of digital classrooms in Surabaya, focusing on the readiness of teachers and students, the challenges encountered, and the adaptation strategies employed. The research method used is qualitative with a case study approach, involving in-depth interviews, participatory observations, and document analysis at several schools in Surabaya. The results indicate that the success of digital learning is significantly influenced by access to technology, teacher training, and adequate institutional support. Despite challenges such as the digital divide, network disruptions, and psychological barriers, teachers and students have been able to develop various learning innovations and adaptation strategies to enhance the effectiveness of the teaching and learning process. This study underscores the importance of collaboration among all stakeholders in creating an inclusive and sustainable digital education ecosystem. The findings have implications for the development of future education policies and digital learning practices.